2016
DOI: 10.1038/ncomms10716
|View full text |Cite
|
Sign up to set email alerts
|

A Helitron transposon reconstructed from bats reveals a novel mechanism of genome shuffling in eukaryotes

Abstract: Helitron transposons capture and mobilize gene fragments in eukaryotes, but experimental evidence for their transposition is lacking in the absence of an isolated active element. Here we reconstruct Helraiser, an ancient element from the bat genome, and use this transposon as an experimental tool to unravel the mechanism of Helitron transposition. A hairpin close to the 3′-end of the transposon functions as a transposition terminator. However, the 3′-end can be bypassed by the transposase, resulting in transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
121
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(127 citation statements)
references
References 53 publications
5
121
0
1
Order By: Relevance
“…Mutagenic transposon vectors can also be directly introduced into animal models, either by microinjection of the transposon components into early embryos or by mobilizing chromosomally resident transposons upon crossing of transgenic animal stocks encoding the different components of the transposon systems. One recent addition to the transposon toolbox is the Helraiser transposon that has been resurrected from ancient Helitron elements in the bat genome [135]. The fundamental difference to all other transposons that were described in this article is that Helitron elements transpose through a “copy-and-paste” reaction, in which the donor element does not excise, but it generates progeny that integrates elsewhere in the genome.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Mutagenic transposon vectors can also be directly introduced into animal models, either by microinjection of the transposon components into early embryos or by mobilizing chromosomally resident transposons upon crossing of transgenic animal stocks encoding the different components of the transposon systems. One recent addition to the transposon toolbox is the Helraiser transposon that has been resurrected from ancient Helitron elements in the bat genome [135]. The fundamental difference to all other transposons that were described in this article is that Helitron elements transpose through a “copy-and-paste” reaction, in which the donor element does not excise, but it generates progeny that integrates elsewhere in the genome.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Grabundzija and others confirmed the ‘end-bypass’ model of gene capture in Helitrons, in which the transposase skips the 3’ terminus and thus includes 3’ flanking DNA sequence in the excised Helitron. Finally, Grabundzija and others demonstrated that canonical Helitrons occur as a circular intermediate [14], as has been observed previously for the Insertion Sequence IS91 in Escherichia coli [23]. Transposition via a circular intermediate can also explain the presence of multiple tandem insertions of truncated Helitrons that have recently been found in plant centromeres [24].…”
Section: Introductionmentioning
confidence: 63%
“…A recent study using a reconstructed ancestral bat Helitron1 sequence provided important insights into the mechanisms underlying transposition and gene capture in canonical Helitrons [14]. First of all, the authors could demonstrate that Helitrons transpose as single stranded DNA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations